Genetic Determinants of Antibiotic Resistance in Francisella - Kassinger, Stephen J.; van Hoek, Monique L. (Frontiers in Microbiology, 2021)
Tularemia, caused by Francisella tularensis, is endemic to the northern hemisphere. This zoonotic organism has historically been developed into a biological weapon. For this Tier 1, Category A select agent, it is important to expand our understanding of its mechanisms of antibiotic resistance. Francisella is unlike many gram-negative organisms in that it does not have significant plasmid mobility, and does not express antibiotic resistance mechanisms on plasmids; thus plasmid-mediated resistance does not occur naturally. It is possible to artificially introduce plasmids with antibiotic resistance markers for cloning and gene expression purposes. In this review we survey both the experimental research on antibiotic resistance in Francisella as well as bioinformatic databases which contain genomic and proteomic data. We explore both the genetic determinants of intrinsic antibiotic resistance as well as naturally acquired or engineered antimicrobial resistance and phenotypic resistance in Francisella. Herein we survey resistance to beta-lactams, monobactams, carbapenems, aminoglycosides, tetracycline, polymyxins, macrolides, rifampin, fosmidomycin, and fluoroquinolones. We also highlight research about the phenotypic antibiotic resistance difference between planktonic and biofilm Francisella. We discuss newly developed methods of testing antibiotics against Francisella which better involve the intracellular nature of Francisella infection and may better reflect the eventual clinical outcomes for new antibiotic compounds. Understanding the genetically encoded determinants of antibiotic resistance in Francisella is key to optimizing the treatment of patients and potentially developing new antimicrobials for this dangerous intracellular pathogen.